The age of sustainable development - Medeiros, E. (Journal of Geography, 2019)
The work of Jeffrey Sachs on world development, global macroeconomics, and the fight against poverty is vast and, in my view, widely relevant for providing a global perspective of these processes. But, more important, his work is influential in providing alternative visions to solving global environmental problems by advocating the importance of sustainable development paths for policy implementation, namely within the United Nations, and as an advisor to several heads of state and governments across the world. Hence, and despite being three years old and widely reviewed upon publication, I consider that the content of the book embraces fundamental questions for the future of humankind, making it an important book that should be revisited. Moreover, this book is especially interesting and relevant since the concept of sustainable development is gaining worldwide acceptance, due to an overwhelming recognition of the impacts of human activities and rising population on global warming, environmental pollution, and natural resources degradation.